ICA UNICA variedad de papa para procesamiento y consumo fresco. - Hernández Castillo, Edgar; Rodríguez B., Armando; Pineda C., Ramón; Valbuena B., Iván; Estrada R., Nelson (Instituto Colombiano Agropecuario - ICA, 1995)
Papa-Solanum tuberosum